The Impact of Fiscal Expenditure and Technological Innovation on High Quality Economic Development - Zhou, Zejiong; Lu, Wenhui (International Journal of Social Sciences and Public Administration, 2025)
In order to explore the mechanism and transmission path between fiscal expenditure, scientific and technological innovation and high-quality economic development, based on the connotation of fiscal expenditure, scientific and technological innovation and high-quality economic development and related theoretical basis, this paper discusses the theoretical mechanism of fiscal expenditure and scientific and technological innovation affecting high-quality economic development and the panel data of 31 provinces in China from 2013 to 2022, and uses spatial econometric model to analyze the impact of fiscal expenditure and scientific and technological innovation on high-quality economic development. The results show that fiscal expenditure has a spatial spillover effect on high-quality economic development.